O-025 Sound measurement in patient-specific 3D printed bench models for venous pulsatile tinnitus. (22nd July 2019) - Amans, M; Valluru, K; Haraldsson, H; Kao, E; Leach, J; Wright, A; Ballweber, M; Meisel, K; Saloner, D
Abstract : Introduction: Pulsatile tinnitus (PT) can be caused by aberrant blood flow in large cerebral veins near the cochlea. In our previous works we evaluated flow patterns in patient's cerebral venous sinuses to try and identify patterns of flow unique to symptomatic PT patients. However, the exact mechanism of sound production remains unclear. In order to further investigate the sound production mechanism, we created 3D-printed flow models based on patient-specific cerebral venous anatomies. Methods: We performed MR patients with venous etiology of PT recruited from the UCSF Pulsatile Tinnitus Clinic. A surface representation of the venous sinuses from the affected side was segmented from the CE-MRA dataset and modified by adding flow extensions at both ends to facilitate connections to a rotary pump. The lumenal anatomy was printed in wax that was embedded in a degassed solution of silicone encapsulant that was cured for 48 hours. The inner wax lumen was then melted out of the silicone by heating at 120°C creating a durable and rigid patient-specific flow model (figure 1). Models were attached to a pulsatile pump and sound recordings were made using a Bluetooth-compatible electronic stethoscope. Signals were processed and analyzed in MATLAB. Results and discussion: Four total flow models were created from two patients (figure 1). Patient one has a high-riding jugular bulb and stenosis of the internal jugular vein at the level of C1 (figure 1A). An additional modified flow model for this patient was created by computationally removing the stenosis (figure 1B). Other models are from a patient with idiopathic intracranial hypertension and a transverse sinus stenosis (figure 1C). After lowering her ICP via LP, her symptoms resolved, and an additional MRA was performed that was used to generate the post-LP (figure 1D). Conclusions: We have developed patient-specific flow models for venous causes of PT that may be an appropriate in vitro surrogate for venous causes of PT. Disclosures: M. Amans: 1; C; NIH. 2; C; Stryker, Covidien. K. Valluru: None. H. Haraldsson: None. E. Kao: None. J. Leach: None. A. Wright: None. M. Ballweber: None. K. Meisel: None. D. Saloner: 1; C; NIH.